The Petrified Men and the Scarecrow: Substance, Body, and Self-image in Seamus Heaney’s Bog Poems - Pap, József (Hungarian Journal of English and American Studies, 2021)
Seamus Heaney’s poetry was engaged with violence for decades. His artistic exploration of land and fossils revolved around the same questions: to what extent can a human being move himself away from an inherent “tribalism”? To what extent is identity inherited through history and what rights, responsibilities come with it? These questions arose in the author’s oeuvre when the horrors of civil war reached their peak in Northern Ireland. The issues of shared community not only played a significant role in the development of self-identification, they also meant the survival of the sectarian conflict. Starting with the first bog-poems, Heaney was keen on producing a mythology to serve identity, and sometimes allowed his political opinion to filter through the images of Stone Age remains from the bog. For scientists, the investigation of archeological finds means relying on methods such as the necessary carbon analysis and careful identification of evidence, as to who these bodies were, when they lived, what characterized their daily routines, and the times they lived in. The same findings, however, had a different impact on Heaney. He used the metaphor of the land of these ancient bodies, and of history, to engage with the question of identity, but criticism made him reconsider what position he should take on the morality of the given past society. At the same time the poet, who voluntarily shared common roots with these long-forgotten forbears, was the one who started deconstructing their moral heritage in the works written towards the end of his poetic oeuvre. In contrast to earlier poems on bog-bodies, “Tollund” from the 1996 collection, The Spirit Level, and “Tollund Man in Springtime” from 2006, reflect a forward-looking attitude in which Heaney left behind an apologist viewpoint for sectarian violence. (JP)